Chemical Literacy of High School Students: Analysis of Cognitive Abilities on Colloid Material - Mellyzar Mellyzar; Isna Rezkia Lukman; Sirry Alvina; Ali Imron Pasaribu; Mhd. Ridwan Fadli (Postgraduate, University of Mataram, 2022)
The development of science, technology, and society requires humans to have skills beyond literacy and numeracy that are needed to survive. Scientific literacy is the focus of learning in the 21st century. Currently, the scientific literacy index of students in Indonesia is still low. Chemistry is a part of science. Chemical literacy is the ability of students to identify, analyze, and process chemical concepts to solve everyday problems and communicate scientifically the chemical phenomena that occur around them. Colloidal material in chemistry learning has some abstract concepts close to everyday life. So the purpose of this study was to determine the chemical literacy ability of students on colloidal material in North Aceh and Lhokseumawe. The subjects of this study were 217 students of class XII, in SMA North Aceh and Lhokseumawe. The instrument used in this study is a chemical literacy question in the form of a description consisting of 8 PISA standard chemical literacy questions. The result of this research is that the highest student answers are on the literacy scale with nominal criteria, while the lowest is multidimensional criteria. According to the distribution of chemical literacy scores in the Aceh region, the highest was in the medium-grade category with 142 students, and the lowest was in the high-grade category with 14 students.